Avaliação de sistemas de informação: o papel da competência dos usuários para o uso do sistema eletrônico de informações (SEI) em uma organização pública de saúde - Paulino, Vanessa Carreiro (2024)
This research aims to analyze how user competence influences the use of the Electronic Information System (SEI) in a Public Health Organization. To achieve this objective, the following guiding question is proposed: What is the influence of user competence on the use of the Electronic Information System (SEI) in a Public Health Organization? For this purpose, it was necessary to contextualize the theme of the SEI, present the concept of competence, make a presentation on the analysis of information systems and construction of the model for the study. The EDCRUS, TAM and Use of information systems models were used. The paper proposes a model that includes the analysis of user competence for using SEI, with the application of a questionnaire composed of 60 items with 5-point Likert scales, through the six dependent variables: General operations with documents, General operations with processes, Initial procedures in SEI, Special resources and external users, Perceived ease of use, Perceived usefulness of use and the independent variable: Use. The questionnaire was applied online, through an electronic form, with health professionals from a Public Health Organization in the cities of João Pessoa, Campina Grande and Cajazeiras, all in the state of Paraíba, after approval by CEP/UFPB, through Opinion no. 6,682,009. The data obtained from a total of 211 respondents, of which 159 questionnaires were considered valid, suggest that the proposed model has evidence of validity and reliability, based on content validity, convergent validity (variance extracted above 50% in all constructs) and internal consistency verification (lowest Cronbach's alpha value = 0.79). Added to the significance test of the F statistic and the analysis of the adjusted coefficient of determination, 67.1% of the dependent variable was explained from the six dependent variables. This model is useful for predicting and describing, allowing researchers and professionals to identify the underlying reasons for users not using a system and, thus, implement the necessary corrections. Three of the six proposed hypotheses were not rejected (Special features and external users, Perceived ease of use and Perceived usefulness of use) and the variable Perceived usefulness of use was the one that reached the highest value of , suggesting that perceived usefulness is significantly more related to the use of SEI. The results indicate that the main skills that influence the use of SEI by health professionals are related to attitude, as users use a system when they perceive that its functions are useful, leaving the ease or difficulty of using the tool in the background.